PENGARUH IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DALAM MENINGKATKAN KINERJA ELEMEN SUMBER DAYA MANUSIA ( STUDI KASUS: SMKN KOTA PEKANBARU) - Rusyaidi Thahery (Politeknik Negeri Bengkalis, 2018)
Total Quality Management (TQM) starts from the quality that has been applied by companies to get good quality in the early decades of 2000 in Indonesia. In this study explained TQM Education with the Company's TQM perspective in general which consisted of customer focus, quality obsession, teamwork and school performance. This study aims to determine the implementation of TQM education on the performance of State Vocational High Schools in Pekanbaru City. The method used in this study is descriptive and quantitative. The population of this study was 474 and the sample used a sampling quota of 82 respondents and used multiple linear regression analysis. The results of the TQM Education research namely Customer Focus, Quality Obsession and Team Cooperation did not have a significant effect simultaneously and partially had a significant effect on the performance of the State Vocational High School in Pekanbaru.